Fabrication of magnetostrictive composites using metallic glass as glue. (June 2022) - Lin, Hongji; Yang, Jian; Zhao, Hui; Gou, Junming; Zhang, Yiqun; Fu, Jianan; Sun, Fei; Ruan, Wenqing; Zhang, Zhenxuan; Liang, Xiong; Ren, Shuai; Ma, Tianyu; et al.
Abstract: With the continuous expansion of the applications in complex environments, magnetostrictive materials are required to possess not only high performance but also tunable performance. A promising way to achieve this goal is to form composites by combining two or more materials together. However, high performance magnetostrictive composites are still rare, in particular, in a pure metallic form. In this work, we develop a facile and efficient method by using metallic glass as glue, to fabricate pure metallic magnetostrictive composites with high and tunable performance. The Terfenol-D/metallic glass magnetostrictive composites are obtained by a unique thermoplastic forming method under a low temperature (480 K), small stress (114 MPa) and short time (3 min), which exhibit a relatively large field induced magnetostriction (∼650 ppm under a magnetic field of 30 kOe) and compressive strength (∼185 MPa). Thus, this work provides a promising strategy to design new magnetostrictive materials as well as other metal matrix composites with particular properties. Highlights: A new kind of metallic-glass-bonded bulk magnetostrictive composite is fabricated. The obtained composites exhibit a relatively high magnetostriction and good mechanical properties. The composites are obtained by a facile and effective "metallic glue" method which utilizes the metallic glass as glue. This method allows the properties of the composite to be finely tuned according to the composition design. The required condition of this method is very convenient, including a low temperature, small stress and very short time.